2007
DOI: 10.3171/jns.2007.106.4.621
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and long-term safety of deep brain stimulation in the treatment of movement disorders

Abstract: The authors conclude that in their 10-year experience, DBS has proven to be safe for the treatment of medically refractory movement disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
107
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(118 citation statements)
references
References 39 publications
8
107
2
1
Order By: Relevance
“…18 Other series have shown that hardware complications like lead fracture, infection, skin erosion, and cable connection failure occur in up to one-quarter of patients. 40 Okun et al 29 found suboptimally placed electrodes in 46%, inadequate follow-up programming in 17%, and suboptimal DBS parameters in 37% of the cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Other series have shown that hardware complications like lead fracture, infection, skin erosion, and cable connection failure occur in up to one-quarter of patients. 40 Okun et al 29 found suboptimally placed electrodes in 46%, inadequate follow-up programming in 17%, and suboptimal DBS parameters in 37% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Protein denaturation or coagulative necrosis occurs in the cells at a temperature of 56°C for 1 second. 18 Because sound produces an alternating rarefaction, this generates acoustic cavitation. The skull presents a high acoustic impedance to the ultrasound as it absorbs and reflects the waves.…”
mentioning
confidence: 99%
“…Battery replacements were excluded as a cause of surgical revision, since they are not adverse events but expected occurrences related to the long-term use of the internal pulse generators (IPG) [14,15]. We also excluded patients with complications during the implantation surgery, and the immediate (≤2 weeks) postoperative period, as they have already been reviewed elsewhere [6]. Due to the retrospective nature of this study no IRB approval was required.…”
Section: Methodsmentioning
confidence: 99%
“…Although various intra- and postoperative complications have been described in patients treated with DBS [6,7,8,9] those associated with hardware malfunction or infection carry a higher morbidity [10,11] as they usually require surgical revision of the implants or device removal, compromising long-term benefits and increasing health-care costs [10,11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…5,9,12,23,24,27,31,33,34 Most of these studies are retrospective analyses of a single institutional experience, limiting the ability to generalize conclusions owing to inherent selection bias. Previous multicenter studies also have inherent limitations given their focus on a particular region and the small number of centers.…”
mentioning
confidence: 99%